Los diez mínimos para los egresados de secundaria - Trahtemberg Siederer, León (2010)
Although the goals of schooling tend to refer toa comprehensive education that interacts with an out-of-school reality and that prepares children and youngsters for life outside school, the reality shows that the curricular contents and skills that are. nourished at school are essentially intra-school, intellectual and academicals.This article proposes 1 O additional educational experiences to give students an idea of the out-of-school reality, one approach that is more oriented to meet the out-of-school requirements that will challenge the student once school years are over.